The fight against unfair competition in Poland in the years 1918-1939 - Dolata, Tomasz (University of Wroclaw. Faculty of Law, Administration & Economics, 2012)
The most important aspects concerning the combating of unfair competition in pre-war Poland are analysed in this study: factors determining the necessity of introducing a uniform, common legal regime binding across the whole territory of Poland are discussed, the genesis of the Polish law combating unfair competition of 2.08.1926 are examined, certain shortcomings of the law, which led to the revision of the act, in 1927, are characterized, attention is paid to the positive acceptance of the law by Polish and foreign doctrine (French and German ).
Keywords: Polska (1918-1939); zwalczanie nieuczciwej konkurencji